El ejemplo de Lucrecia en el "De institutione feminae christianae" de Juan Luis Vives - Marina Sáez, Rosa María (Euphrosyne: Revista de filología clássica, 2019)
In this paper the exemplum of Lucretia in Luis Vives’ De Institutione feminae christianae is analysed in his double facet as a lanifica and pudica woman. Although Vives knew well the interpretation of this exemplum that appears in the Augustine’s City of God, the main source on the subject of the defence of chastity is Saint Jerome, author much more rigorous in regard to that question.